Legal technique of the new Criminal Code Republik of Kazakhstan - Ozbekov, D.O.; Zhumasheva, A.T. (Publ.KarSU, 2017)
This article is dedicated to analysis of the methods of legal technique used in the Criminal Code of 2014 of the Republic of Kazakhstan. The legislative definition of legal technique of legal acts, conditioned by the dynamic trends of improvement of legislation, which requires to minimize the spontaneity of legislative work, improve coherence level, consystency of existing legislation. An analysis of the historical development of legislative techniques showed that there is succession in the forms of law, in the ways and means of legal expression in the systematics of right, the external design of the normative act. Rules that are reviewed by authors, related to the content and form of criminal laws (mixed formal-evaluationary techniques, differantiation of general and specific parts of the Code, the establishment of classifications of criminal acts within specific parts of the Criminal Code, the methods of reception, ratification and referencing in accordance with international standards). Among the features of the legislation following expressions are marked: change of numeration points; the highlighting of the self-sufficient a separate structural and compositional elements, that contain the interpretation of certain terms (Article 3 of the Criminal Code); change of the number and nature of the notes to the articles of the Criminal Code.
Юридическая техника нового Уголовного кодекса Республики Казахстан
Қазақстан Республикасының жаңа Қылмыстық кодексінің заң техникасы
Keywords: Criminal Code of the Republic of Kazakhstan in 1997; the Criminal Code of the Republic of Kazakhstan in 2014; legal technique; legislative technique; an explanation of the concepts contained in the Criminal Code; note to the article of the Special part Criminal Code